Effectiveness of a Tele-Ophthalmology Vision Center in Treating Corneal Disorders and Its Associated Economic Benefits. Issue 6 (8th June 2022) - Komal, Sangoi; Radhakrishnan, Naveen; Vardhan S, Ashok; Prajna, N. Venkatesh
Abstract : Purpose: The aim of this study was to study the clinical and economic impact of a teleophthalmology-based vision center (VC) in the management of corneal diseases in rural south India. Methods: Data of patients with corneal disorders who visited the VC in the year 2019 were analyzed for the total number of outpatient visits, the proportion of corneal cases that were treated at the VC, those referred to the base hospital (BH), and the costs of treatment. Results: In 2019, 1131 (10%) of 10, 850 patients who visited the VC were diagnosed with corneal disorders. Of these, 950 (84%) patients were treated at the VC itself and did not require to be referred. The remaining 181 (16%) were referred to the BH. Of these 1131 patients, 836 (74%) patients presented with a painful acute corneal disorder. The most common painful acute corneal disorders included corneal foreign body (376, 33%), epithelial abrasions (205, 18%), and infectious keratitis (124, 11%). A patient can save approximately a minimum of INR 1200 (USD 16) by attending the VC rather than the BH. In 2019, by treating 950 patients, the VC saved approximately INR 114, 0000 (USD 15, 200) for the community. A similar calculation extrapolated to a 10-year period (2009–2019) revealed that by providing care for these corneal disorders at the community level, the VC saved approximately INR 705, 8400 (USD 94, 112) for the community. Conclusions: VC reduces the barriers to care by increasing the accessibility and affordability of treatment for patients with corneal disorders, resulting in a significant cost saving to the community.